(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Food irradiation has been approved in more than 60 countries for many applications in a wide variety of foods. 2-Alkylcyclobutanones (2-ACBs) are the only known radiolytic products formed when food containing fatty acids are irradiated. Despite the importance of food irradiation, the toxicological potential of 2-ACBs in irradiated food is still no fully understood. In this study we investigated the cytotoxic effects of irradiated palmitic and stearic fatty acids byproducts, 2-dDCB and 2-tDCB, in the hepatic cells (HepG2, BRL3A and HTC). The cytotoxic effects of 2-dDCB and 2-tDCB were evaluated at 100, 300 and 500 μM for 24 and 48 hours and the cell viability was measured using the MTS assay. While no toxicity was observed for 2-tDCB in all cells for all tested conditions, 2-dDCB was found to be toxic in BRL3A cells (at 100 µM after 48 hours) and HTC cells (at 24 hours in all tested concentrations). HepG2 cells on the other hand, were found to be resistant to 2-dDCB-induced toxicity. Overall our data shows that the byproduct 2-tDCB is not toxic for hepatic cells while 2-dDCB can be used has a potential marker for food irradiation-induced toxicity.